The Influence of Emotional Intelligence and Work Motivation on Employee Performance at the National Unity and Politics Agency (Kesbangpol) of Banggai Laut Regency - Eef Saifullah Doloan (Economics and Digital Business Review, 2026)
This study examines the influence of emotional intelligence and work motivation on employee performance at the Regional Office of the National Unity and Political Agency (Badan Kesatuan Bangsa dan Politik) of Banggai Laut Regency. The study aims to determine whether emotional intelligence and work motivation have partial and simultaneous effects on employee performance, as well as to identify the variable with the most dominant influence. This research employed a quantitative approach using a field research method through interviews, questionnaires, documentation, and literature review. The data were analyzed using statistical techniques, including Analysis of Variance (ANOVA) or the F-test. The findings indicate that emotional intelligence has a positive and significant effect on employee performance. Work motivation is also proven to have a positive and significant effect on employee performance. Furthermore, work motivation was found to be the most dominant variable influencing employee performance. Simultaneous testing revealed that emotional intelligence and work motivation jointly have a positive and significant effect on employee performance. Based on these findings, improving employee performance within the organization requires greater attention to both emotional intelligence and work motivation. Strengthening self-awareness, interpersonal skills, motivational support, and a supportive work environment can help employees perform more effectively and achieve organizational goals